Leveraging the Asset Administration Shell for Agent-Based Production Systems. Issue 1 (2021) - Ocker, Felix; Urban, Chris; Vogel-Heuser, Birgit; Diedrich, Christian
Abstract: In a world that is subject to trends such as customization, production systems have to become increasingly flexible. The agent paradigm seems like a promising approach to create intelligent production systems with the required flexibility. So far, the creation of agent-based systems has been a challenge for engineers though. This is due to the additional effort for designing the system, and the challenge of creating appropriate knowledge bases for the agents. This paper discusses how this challenge can be addressed by leveraging digital twins to create agent-based production systems at the example of the Asset Administration Shell.